2008
DOI: 10.1038/cr.2008.53
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Arabidopsis thaliana NAC transcription factors ANAC019 and ANAC055 in regulating jasmonic acid-signaled defense responses

Abstract: npg Jasmonic acid (JA) is an important phytohormone that regulates plant defense responses against herbivore attack, pathogen infection and mechanical wounding. In this report, we provided biochemical and genetic evidence to show that the Arabidopsis thaliana NAC family proteins ANAC019 and ANAC055 might function as transcription activators to regulate JA-induced expression of defense genes. The role of the two NAC genes in JA signaling was examined with the anac019 anac055 double mutant and with transgenic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
252
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(266 citation statements)
references
References 44 publications
8
252
2
4
Order By: Relevance
“…The bZIP family in plants includes master regulators of salicylic and abscisic acid (ABA) hormone responses (Finkelstein and Lynch, 2000). ANAC055 is downstream of ABA and jasmonic acid signaling pathways and affects abiotic growth responses (Bu et al, 2008). HB family members play important roles in water stress and interact directly with auxin regulation (Ré et al, 2014).…”
Section: Dap-seq Captures Tf Binding Sites Identified By Chip-seqmentioning
confidence: 99%
“…The bZIP family in plants includes master regulators of salicylic and abscisic acid (ABA) hormone responses (Finkelstein and Lynch, 2000). ANAC055 is downstream of ABA and jasmonic acid signaling pathways and affects abiotic growth responses (Bu et al, 2008). HB family members play important roles in water stress and interact directly with auxin regulation (Ré et al, 2014).…”
Section: Dap-seq Captures Tf Binding Sites Identified By Chip-seqmentioning
confidence: 99%
“…Hill, S. Ott, and V. Buchanan-Wollaston, unpublished data). Furthermore, ANAC055 acts downstream of MYC2 in JA-mediated defense against B. cinerea (Bu et al, 2008), and clusters 24, 26, 27, and 28 are all overrepresented for genes differentially expressed in a MYC2 knockout line (P < 0.01), suggesting this TF is a common upstream regulator. The activity of MYC2 is controlled by binding to JAZ proteins (Chini et al, 2009); consistent with this, MYC2 is not differentially expressed during B. cinerea infection and hence is itself not included in any cluster.…”
Section: Causal Structure Identification Network Modeling Highlights mentioning
confidence: 99%
“…However, recent studies have indicated that this family of TFs also plays crucial roles in the response to biotic stress. Transgenic lines with reduced or increased expression of ANAC002, ANAC019, ANAC055, ANAC081, and ANAC092 have altered susceptibility to pathogen infection (Delessert et al, 2005;Bu et al, 2008;Carviel et al, 2009;Wang et al, 2009;Wu et al, 2009) and all are differentially expressed following B. cinerea infection. Binding sites for NAC TFs are significantly overrepresented in a cluster of genes induced between 18 and 24 HAI with additional enrichment in clusters with similar expression profiles.…”
Section: Specific Tf Binding Motifs Are Enriched In Groups Of Coexprementioning
confidence: 99%
“…Plants individually overexpressing these genes showed a significant increase in drought tolerance or salt tolerance [23][24][25][26]. The anac019anac055 double mutant showed increased resistance to B. cinerea compared with the wild-type plants, and transgenic plants overexpressing ANAC019 or ANAC055 showed decreased resistance to this pathogen [27]. Moreover, NAC transcription factors such as ATAF2 and OsNAC6 have been shown to be involved in both biotic and abiotic stress responses.…”
Section: Introductionmentioning
confidence: 99%